Philosophy of education in a new key: Future of philosophy of education. Issue 8 (9th June 2022) - Tesar, Marek; Hytten, Kathy; Hoskins, Te Kawehau; Rosiek, Jerry; Jackson, Alecia Y.; Hand, Michael; Roberts, Peter; Opiniano, Gina A.; Matapo, Jacoba; St. Pierre, Elizabeth Adams; Azada-Palacios, Rowena; Kuby, Candace R.; et al.
Abstract: What is the future of Philosophy of education? Or as many of scholars and thinkers in this final 'future-focused' collective piece from the philosophy of education in a new key Series put it, what are the futures—plural and multiple—of the intersections of 'philosophy' and 'education?' What is 'Philosophy'; and what is 'Education', and what role may 'enquiry' play? Is the future of education and philosophy embracing—or at least taking seriously—and thinking with Indigenous ethicoontoepistemologies? And, perhaps most importantly, what is that 'Future'? These debates have been located in the work of diverse scholars: from the West, from Global South, from indigenous thinkers. In this collective piece, we purposefully juxtapose (and do not categorise under forced headings) diverse takes on the future of these intersections. We have given up the urge to organise, place together, separate with subheadings or connect the paragraphs that follow. Instead, we let these philosophers of education and thinkers who use philosophical texts and ideas to sit together in one long read as potentially 'strange and unusual bedfellows'. This text urges us to understand how these scholars and thinkers perceive our educational philosophical futures, and how the work and thinking they have done on thinking about what the future of that new key in philosophy of education may look like is embedded in a much deeper and richer literature, and personal experience.